Respostas

  • Usuário do Brainly
2014-06-23T11:48:26-03:00
 \sqrt{3x+6} =x+2

( \sqrt{3x+6}  )²=(x+2)²

3x+2=x²+4x+4
x²+x+2=0
Δ=1+8=9
√Δ=3

X'= \frac{-1+3}{2}  =  \frac{2}{2}  = 1

x"= \frac{-1-3}{2} =  \frac{-4}{2}  = -2

verificação
p/x=1

 \sqrt{3(1)+6} = 1+2

 \sqrt{9} =3

3=3  V

p/ x=-2

 \sqrt{3(-2)+6}  = -2+2

 \sqrt{0}  = 0   V

S={-2,1}



b)  \sqrt{4x+1}  = 2x-1

( \sqrt{4x+1} )² =( 2x-1

4x+1 =4x² -4x+1

4x² -8x=0
4x(x-2)=0
4x=0
x=0

x-2=0
x=2

verf/

p/ x=0

 \sqrt{4(0)+1} =2(0) -1

1≠-1

p/ x=2

 \sqrt{4(2)+1} =2(2)+1

 \sqrt{9} =3

3=3  V

S={2}


1 4 1